The crime of child abduction in light of regional international agreements - Djeghri, Amira (Journal of Human Sciences, 2023)
The crime of child abduction is one of the most serious crimes against humanity, as it targets a vulnerable group that is unable to protect itself by itself. These acts through the conclusion and establishment of agreements that define the rights of the child and prohibit crimes against him and lay down the necessary means to be taken to protect him from what is known as organized crime affecting children, where in addition to national legislation and international agreements there are many agreements, treaties and international regional organizations, whether African or European or Arab, in turn, aims to preserve and protect the child from various crimes against him, especially the crime of kidnapping.